Intestinal parasites co-infection among tuberculosis patients in Ethiopia: a systematic review and meta-analysis - Alemu, Ayinalem (BMC Infect Dis, 2020)
BACKGROUND: Tuberculosis and intestinal parasites are mostly affecting poor people. They are in a vicious since one is the risk factor for the other. However, the comprehensive report on the burden and co-incidence of intestinal parasites and tuberculosis in Ethiopia is scant. This systematic review and meta-analysis aimed to provide abridge conclusive evidence on the intestinal parasite-tuberculosis co-infection in Ethiopia. METHODS: A total of 414 articles published in English were searched from both electronic databases (CINAHL, DOAJ, Embase, Emcare, Medline, ProQuest, and PubMed, Science Direct, and Web of Science) and other sources. The qualities of the included studies were assessed using the Joanna Briggs Institute Critical Appraisal tools and the publication bias was measured using the funnel plot and Eggers regression test. Comprehensive meta-analysis (CMA) Version 3.3.07 and Review Manager software were used to estimate pooled prevalence and associations of intestinal parasites and tuberculosis infection. RESULTS: Eleven articles with a total of 3158 tuberculosis patients included in the analysis based on the eligibility criteria. The estimated pooled prevalence of intestinal parasites co-infection was 33% (95% CI: 23.3, 44.3) using the random-effects model. The most common intestinal parasites were Ascaris lumbricoides 10.5% (95% CI: 6.0, 17.5), Hookworm 9.5% (95% CI: 6.10, 14.4), Giardia lamblia 5.7% (95% CI: 2.90, 10.9) and Strongyloides sterocoralis 5.6% (95% CI: 3.3, 9.5). The odds of intestinal parasites infection was higher among tuberculosis patients compared to tuberculosis free individuals (OR = 1.76; 95% CI: 1.17, 2.63). A significant difference was observed among TB patients for infection with intestinal helminths (OR = 2.01; 95% CI: 1.07, 3.80) but not for intestinal protozoans when compared with their counterparts. The odds of multiple parasitic infections was higher among tuberculosis patients (OR = 2.59, 95% CI: 1.90, 3.55) compared to tuberculosis free individuals. However, intestinal parasites co-infection was not associated with HIV status among tuberculosis patients (OR = 0.97; 95% CI: 0.71, 1.32). CONCLUSION: One-third of tuberculosis patients are co-infected with one or more intestinal parasites, and they are more likely to be infected with intestinal helminths and multiple intestinal parasitic infections compared to TB free individuals. We recommend routine screening of tuberculosis patients for intestinal parasites. The effect of mass deworming on tuberculosis incidence would be important to be considered in future researches. TRIAL REGISTRATION: Registered on PROSPERO with reference number ID: CRD42019135350.